Efficacy of Enhanced Cytokine-Induced Killer Cells as an Adjuvant Immunotherapy for Renal Cell Carcinoma: Preclinical and Clinical Studies. (8th September 2021) - Yang, Yang; Wang, Run-Qing; Zhong, Yi-Ming; Meng, Ming-Yao; Zhao, Yi-Yi; Yang, Li-Rong; Li, Lin; Hou, Zong-Liu
Abstract : Cytokine-induced killer (CIK) cells have been proved to be an effective method of tumor immunotherapy in numerous preclinical and clinical studies. In our previous study, a new method was developed to prime and propagate CIK cells by the combination of IL-2 and IL-15, and this kind of CIK cells had enhanced antitumor effect on lung cancer. For renal cell carcinoma (RCC), immunotherapy plays an important role because of the poor efficacy of radiotherapy and chemotherapy. In this study, we further evaluated the antitumor effects of these enhanced CIK cells against RCC. Enhanced CIK cells were generated by IL-2 combined with IL-15 and identified by flow cytometry. HEK-293 and ACHN cell lines were used to verify the efficiency of CIK cells in vitro, and then the ACHN tumor xenograft model was also employed for in vivo study. In addition, the secreted cytokines including IFN- γ, granzyme B, TNF- α, and perforin, as well as the local microstructure were also studied. Subsequently, 20 patients with RCC were enrolled into our study, and 11 patients were randomly divided into the autologous CIK treatment group for clinical research. The results showed that enhanced CIK cells exert better antitumor effects in RCC in vitro (p < 0.01 in HEK-293 and p < 0.05 in ACHN）and in vivo (p < 0.05 ). Patients benefit overall survival from enhanced CIK therapy in our clinical study. Our present preclinical and clinical studies for the first time elucidated that these enhanced CIK cells would be used as an effective adjuvant therapy in the treatment of RCC.